Low nicotine addiction level, older age, and being female are associated with contemplation and preparation stages of smoking cessation among adult current smokers in Malaysia - Ling, Jane Miaw Yn; Lim, Kuang Hock; Mohd Yusoff, Muhammad Fadhli; Ab Rahman, Jamalludin; Ab Rahman, Norny Syafinaz; Draman, Samsul; Tee, Guat Hiong; Kartiwi, Mira; Nik Mohamed, Mohamad Haniki; Ho, Bee Kiau; Chan, Caryn Mei Hsien; Wee, Lei Hum; et al. (Malaysian Medical Association (MMA), 2017)
Introduction: Increasing the cessation rate among smokers was among the effective strategies to reduce smoking related health problems. Identification of stages of smoking cessation among smokers is a pre-requisite to enhance the rate of smoking cessation. The aims of the study were to determine the prevalence and factor/s associated with stages of smoking cessation across demographic distribution of adult current smokers in Malaysia. Methodology: Data were derived from a population based study carried out from April 2016 to July 2016. The study involved a representative sample of Malaysian adults aged 18 years and above. Face to face interviews were carried out by trained researchers using pre-validated standard questionnaire to obtain data from respondents. Multivariable logistic regression analysis was used to determine the association between socio-demographic variables, nicotine addiction level and electronic cigarette (ECV) usage with stages of smoking cessation. Results: Among 438 current smokers, approximately 60% (n=269/438) were in the pre- contemplative stage and 40% (n=169/438) were in the contemplative and preparation stages of smoking cessation. The proportion of pre-contemplation were higher among smokers with higher nicotine addiction level (71.3%), lower education attainment (71.4%), and those who were single/widowed/divorced (66.9%). Multivariable analysis showed that males (AOR, 5.32; 95 CI 1.16-24.39), and those with low to high level of nicotine addiction (AOR 2.10; 95 CI 1.37-3.21) were more likely to be in pre-contemplation stage whilst those of older age groups were more likely to be in advance stage of smoking cessation (AOR.0.57; 95 CI 0.37-0.88). Conclusion: The study revealed that majority of current smokers in Malaysia have no intention to quit smoking within 6 months (pre-contemplation stage). Specific interventions targeting males, young adults and smokers with low to high nicotine addiction should be introduced to ensure the smokers proceed to the advanced stage of smoking cessation.